Pengaruh Lingkungan Kerja Dan Kompensasi Terhadap Turn Over Intentions Karyawan PT. Primajasa Perdanaraya Utama Tasikmalaya (Survei Pada Karyawan PT. Primajasa) - Moch Faisal Akbar; Rita Tri Yusnita; Suci Putri Lestari (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This study aims to determine the simultaneous and partial effect of the Work Environment and Compensation on Turnover Intention at PT. Primajasa Perdanaraya Utama Tasikmalaya. The research method used in this study is to use a quantitative research method with a survey approach. The population in this study are employees of PT. Primajasa Perdanaraya Utama Tasikmalaya with 70 employees. The types of data used in this research are primary data and secondary data. The data testing technique used in this study uses the validity test, reliability test and classic assumption test. Data analysis in this study used multiple regression analysis using SPSS software version 25. The results showed that the Work Environment and Compensation simultaneously had a significant effect on Turnover Intention at PT. Primajasa Perdanaraya Utama Tasikmalaya. The work environment partially has a significant effect on Turnover Intention at PT. Primajasa Perdanaraya Utama Tasikmalaya. Partial compensation has no significant effect on Turnover Intention at PT. Primajasa Perdanaraya Utama Tasikmalaya.